Pro-environmental households and energy efficiency in Spain - Ana Ramos; Xavier Labandeira; Andreas Löschel (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2015)
The residential building sector is a major driver of current and future energy consumption and associated emissions, which can be potentially mitigated through significant energy-efficiency (EE) improvements in both emerging and developed countries. Yet, there are several persistent barriers that hinder the attainment of EE improvements in this area. Using data from a 2008 national representative survey of Spanish households, this paper is interested in the determinants of EE-related decisions. In particular, a discrete-choice model empirically analyzes whether proenvironmental households are more likely to invest in EE and to adopt daily energysaving habits. We show that households with eco-friendly behaviors are more likely to investment in well-differentiated EE measures as well as to steer daily habits towards energy savings. However, no effects are found for households with environmental attitudes based on stated willingness to pay to protect the environment. In addition to this, households belonging to higher income groups and education levels are more likely to invest in EE but not to adopt energy-saving habits; while households with older members are less likely to invest in EE and show fewer eco-friendly habits.
Keywords: Q41; Q48; Q58; 330; energy efficiency; investment; behavior; habits